Two-dimensional XMoSiP2/BP (X= S, Se) Heterostructures as Efficient Photocatalysts for Overall Water Splitting - Somayeh Gholami Rudi; Nayereh Ghobadi; Samaneh Soleimani-Amiri (مجله مدل سازی در مهندسی)
In this article, we investigate the structural, electronic and photocatalytic properties of XMoSiP2/BP (X= S, Se) heterojunctions using density functional theory. The stability of these structures is verified by phonon scattering and formation energy. The potential distribution calculated for different stackings of XMoSiP2/BP heterojunctions indicate the existence of a built-in electric field in these structures. The band diagram shows that these structures have a direct band gap in the range of 0.66 to 1.27 eV. By determining the contribution of BP and XMoSiP2 in the energy band diagram of XMoSiP2/BP, it is shown that the investigated structures have type II band alignment, which renders them as suitable photocatalysts for water splitting. High carrier mobility (up to 9806 cm2 V-1 s-1 for electrons and up to 53500 cm2 V-1 s-1 for holes), anisotropic mobilities in x and y directions, as well as significant difference in mobility of electrons and holes increase the efficiency of these structures as photocatalysts. Optical calculations show that the optical absorption coefficients of XMoSiP2/BP heterostructures are greater than their constituent monolayers in most regions of the solar spectrum, and the high values of absorption coefficients in the visible and ultraviolet regions indicate the high capability of these heterostructures in utilizing the sunlight. Examining the position of the edges of the valence and conduction bands with respect to the redox levels of water shows that two of the proposed heterostructures can be used as good photocatalysts for overall water splitting and simultaneous production of oxygen and hydrogen.